Risk identification and analysis for new energy power system in China based on D numbers and decision-making trial and evaluation laboratory (DEMATEL). (10th April 2018) - Lin, Shuaishuai; Li, Cunbin; Xu, Fangqiu; Liu, Ding; Liu, Jicheng
Abstract: As more new energy power is integrated into the power grid in a large scale, the security problem of the new energy power system (NEPS) has been paid more and more attention in China. Therefore, in order to identify the risk elements of NEPS in China and analyze their internal influence relations, this paper proposes a risk identification and analysis model of NEPS based on D numbers theory and decision-making trial and evaluation laboratory (DEMATEL) method. First, a risk element set is established including new energy resource risk, technical risk, demand side risk, grid side risk and human factor, and Crombach α reliability analysis is introduced to verify the rationality of this set. Then, D numbers theory is employed to integrate the expert evaluation information and the direct relation matrix is obtained. Next, based on DEMATEL method, the cause-effect relations and significance degree of risk elements are analyzed. The results indicate that C10, C15 and C14 are in the top three according to prominence values which are 6.455, 6.186, 5.854 respectively. Meanwhile 18 criteria are divided into 8 causal factors and 10 effect factors which are also analyzed by θ in total relation matrix. Finally, according the risk analysis results, managerial and policy implications are explored. This study concluded that the proposed method provides a strong basis for future academic research. Highlights: We identified 18 risk elements of new energy power system in China. We proposed a risk analysis model based on D numbers theory and DEMATEL method. Risk elements are divided into 8 cause elements and 10 effect elements. C10, C15 and C14 are the most important risk elements which score 6.455, 6.186, 5.854 in prominence degree respectively. Cause-effect relations among risk elements are obtained.